Identification of critical parameters for PEMFC stack performance characterization and control strategies for reliable and comparable stack benchmarking. (14th December 2016) - Mitzel, Jens; Gülzow, Erich; Kabza, Alexander; Hunger, Jürgen; Araya, Samuel Simon; Piela, Piotr; Alecha, Iker; Tsotridis, Georgios
Abstract: This paper is focused on the identification of critical parameters and on the development of reliable methodologies to achieve comparable benchmark results. Possibilities for control sensor positioning and for parameter variation in sensitivity tests are discussed and recommended options for the control strategy are summarized. This ensures result comparability as well as stable test conditions. E.g., the stack temperature fluctuation is minimized to about 1 °C. The experiments demonstrate that reactants pressures differ up to 12 kPa if pressure control positions are varied, resulting in an average cell voltage deviation of 21 mV. Test parameters simulating different stack applications are summarized. The stack demonstrated comparable average cell voltage of 0.63 V for stationary and portable conditions. For automotive conditions, the voltage increased to 0.69 V, mainly caused by higher reactants pressures. A benchmarking concept is introduced using "steady-state" polarization curves. The occurring 20 mV hysteresis effect between the ascending and descending polarization curve can be corrected calculating the mean value of both voltages. This minimizes the influence of preceding load levels, current set points, and dwell times. Highlights: Identification of critical parameters for PEMFC stack benchmarking. Definition of control sensor positions for critical parameters. Parameter variation strategies for sensitivity tests. Summary of test operating parameters for all PEMFC applications. Concept of "steady-state" polarization curve.